Cross-Linking With Diamine Monomers to Prepare Graphene Oxide Composite Membranes With Varying D-Spacing for Enhanced Desalination Properties - Ju, Hong; Duan, Jinzhuo; Lu, Haitong; Xu, Weihui (Frontiers in Chemistry, 2021)
As a new type of membrane material, graphene oxide (GO) can easily form sub-nanometer interlayer channels, which can effectively screen salt ions. The composite membrane and structure with a highwater flux and good ion rejection rate were compared by the cross-linking of GO with three different diamine monomers: ethylenediamine (EDA), urea (UR), and p-phenylenediamine (PPD). X-ray photoelectron spectroscopy (XPS) results show that unmodified GO mainly comprises π-π interactions and hydrogen bonds, but after crosslinking with diamine, both GO and mixed cellulose (MCE) membranes are chemically bonded to the diamine. GO-UR/MCE membrane can achieve similar water flux as the original GO membrane, while the water flux of GO-PPD/MCE and the GO-EDA/MCE dropped. X-ray diffraction results demonstrates that the covalent bond between GO and diamine can effectively inhibit the extension of d-spacing during the change of dry and wet states. The separation performance of the GO-UR/MCE membrane was the best. GO-PPD/MCE has the largest contact angle and the worst hydrophilicity, but its water flux is still greater than GO-EDA/MCE. This result indicates that the introduction of different functional groups while the diamine monomer cross-links graphene oxide will cause some changes in the performance structure of the membrane.